Projected climate change impact on a coastal sea—As significant as all current pressures combined. (6th July 2022) - Wåhlström, Iréne; Hammar, Linus; Hume, Duncan; Pålsson, Jonas; Almroth‐Rosell, Elin; Dieterich, Christian; Arneborg, Lars; Gröger, Matthias; Mattsson, Martin; Zillén Snowball, Lovisa; Kågesten, Gustav; Törnqvist, Oscar; et al.
Abstract: Climate change influences the ocean's physical and biogeochemical conditions, causing additional pressures on marine environments and ecosystems, now and in the future. Such changes occur in environments that already today suffer under pressures from, for example, eutrophication, pollution, shipping, and more. We demonstrate how to implement climate change into regional marine spatial planning by introducing data of future temperature, salinity, and sea ice cover from regional ocean climate model projections to an existing cumulative impact model. This makes it possible to assess climate change impact in relation to pre‐existing cumulative impact from current human activities. Results indicate that end‐of‐century projected climate change alone is a threat of the same magnitude as the combination of all current pressures to the marine environment. These findings give marine planners and policymakers forewarning on how future climate change may impact marine ecosystems, across space, emission scenarios, and in relation to other pressures. Abstract : Our seas are under high pressures from human activities and climate change. The results from this study indicate that end‐of‐century projected climate change alone is a threat of the same magnitude as the combination of all current pressures to the marine environment. We developed methods to incorporate climate change into a cumulative impact model and to bridge some of the knowledge gaps on how sensitive different marine ecosystems are to climate change. These methods can be implemented in other regional seas. It will also facilitate for policymakers to undertake mitigation and adaptation measures and conduct marine spatial planning.